Middle school [compact disc, unabridged] : my brother is a big, fat liar - Patterson, James, 1947- (Patterson, James, 1947- Middle school novels ;, 2013)
Georgia Khatchadorian plans to excel at Hills Village Middle School in all the places her troublemaking brother Rafe failed.